THE EFFECTIVENESS OF EYE MOVEMENT DESENSITIZATION AND REPROCESSING IN TREATING GENERALIZED ANXIETY DISORDER AMONG HIGH SCHOOL STUDENTS - Sarsour, Araa Tariq Morad (An-Najah National University, 2025)
This study investigates effectiveness of Eye Movement Desensitization and Reprocessing (EMDR) therapy on reducing Generalized Anxiety Disorder (GAD) among high school students, Using an experimental design with sample of 60 students, participants were equally divided into an experimental group (30 students) receiving EMDR intervention and control group (30 students) with no intervention, GAD-7 scores measured changes on anxiety levels pre-and post-intervention, Findings reveal notable improvement on experimental group, with reduction on GAD-7 scores indicating an average anxiety decrease of approximately 29%, while control group’s scores showed no significant change, Statistical analysis also examined demographic factors such as gender, monthly income, family education level, and marital status, revealing EMDR's adaptability across these variables, with minimal variation on effectiveness, Study limitations include sample size, short-term follow-up, and reliance on self-reported measures, which may impact generalizability of results, This study highlights EMDR’s potential as an accessible, non- pharmaceutical intervention for adolescent anxiety within school settings, Future research should explore long-term effects of EMDR on larger, more diverse samples to validate findings and examine additional environmental and psychological influences.
فاعلية اإزالة الحساسية وإعادة المعالجة من خلال حركة العين في علاج اضطراب القلق العام لدى طلبة المرحلة الثانوية